Triangulation Applied to Jan H. van Bemmel - Hasman, A.; Bergemann, D.; McCray, A. T.; Talmon, J. L.; Zvárová, J. (Methods of Information in Medicine, 2006)
Objective: To describe the person of Jan H. van Bemmel from different points of view.Method: Triangulation.Results and Conclusions: Jan H. van Bemmel successfully contributed to research and education in medical informatics. He inspired a lot of people in The Netherlands and internationally.
Keywords: Medical informatics; health informatics; education; research